2020
DOI: 10.17221/51/2020-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lupine flour on selected parameters of novel bakery products

Abstract: The aim of the present study was to evaluate the effect of lupine flour on selected parameters of novel bakery products. Different proportions of lupine flour – from 25% to 100% – were added to the baked biscuits; wheat flour biscuits were prepared as the control sample. Increasing lupine content has positively affected mineral concentrations and sensory properties. After 4 days of storage, the lupine biscuit samples showed no significant differences in their water activity values when compared with each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Moreover, the attributes “Well-chewed” and “Bitter” were generated by judges; however, these were not considered in GPA ( Table 4 ). Comparable attributes such as “legume flavor” and “legume aroma” were used to describe biscuits made with lupin flour at a concentration ranging between 25 and 100% [ 10 ]. Similar or identical attributes (such as “crispy,” “chewy,” “tasteless,” “buttery appearance,” and “bitter taste”) were reported in the evaluation of bakery products with lupin flour [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the attributes “Well-chewed” and “Bitter” were generated by judges; however, these were not considered in GPA ( Table 4 ). Comparable attributes such as “legume flavor” and “legume aroma” were used to describe biscuits made with lupin flour at a concentration ranging between 25 and 100% [ 10 ]. Similar or identical attributes (such as “crispy,” “chewy,” “tasteless,” “buttery appearance,” and “bitter taste”) were reported in the evaluation of bakery products with lupin flour [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, sensory evaluation is influenced by different factors such as whether or not there is information about the samples prior to assessment by the panel [ 22 ]. Consumers have reported acceptable mouth feel, appearance, taste, and overall opinion, for bakery products with up to 25% lupin flour [ 10 , 23 ], and up to 40% for chickpea flour [ 4 , 6 , 19 , 24 ]. However, taste and appearance acceptability of pea and green pea flour was reported t ο be lower [ 6 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the results of this study, Jayasena and Nasar-Abbas (2012) reported an improvement in pasta color and consumer acceptability due to the inclusion of lupine flour in the blend, which imparted a desirable yellowish color to the pasta. Štefániková et al. (2020) also reported lupine flour was suitable for fortification in various food products.…”
Section: Resultsmentioning
confidence: 96%
“…Lupine seeds (Lupinus L.) and their products (lupine protein concentrates, lupine grain flour) are non-traditional raw materials that can be used in bread, pastry, biscuits and pasta to improve the nutritional value of the product (Jayasena et al, 2010;Codina et al, 2016;Štefániková et al, 2020). In flour confectionery products lupine grain flour can replace up to 25% of egg solids (Rukshan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%